Hypoxia Moderates γ(1)34.5-Deleted Herpes Simplex Virus Oncolytic Activity in Human Glioma Xenoline Primary Cultures - Friedman, Gregory K (Neoplasia Press Inc., 2012)
Hypoxia plays a critical role in the tumor microenvironment of high-grade gliomas by promoting the glioma stem cell (GSC)-like phenotype, which displays resistance to standard therapies. We tested three glioblastoma multiforme xenograft lines (xenolines) against γ(1)34.5-deleted recombinant oncolytic herpes simplex virus (oHSV) C101 under 1% (hypoxia) and 20.8% (normoxia) oxygen tension for effects on oHSV infectivity, replication, and cytotoxicity in all tumor cells and CD133(+) GSCs. Expression levels of CD133, a putative GSC marker, and CD111 (nectin-1), an adhesion molecule that is the most efficient method for HSV entry, increased significantly under hypoxia in all three xenolines. Despite increased CD111 expression under hypoxic conditions, oHSV infectivity, cytotoxicity and viral recovery were not improved or were diminished in all three xenolines under hypoxia. In contrast, wild-type HSV-1 equally infected xenoline cells in normoxia and hypoxia, suggesting that the 34.5 mutation plays a role in the decreased C101 infectivity in hypoxia. Importantly, CD133(+) cells were not more resistant to oHSV than CD133(-) tumor cells regardless of oxygen tension. Furthermore, CD133 expression decreased as viral dose increased in two of the xenolines suggesting that up-regulation of CD133 in hypoxia was not the cause of reduced viral efficacy. Our findings that oHSV infectivity and cytotoxicity were diminished under hypoxia in several GBM xenolines likely have important implications for clinical applications of oHSV therapies, especially considering the vital role of hypoxia in the microenvironment of GBM tumors.